The Effect of Transformational Leadership on Supporting Total Quality Management (TQM) Initiatives in Commercial Banks in Salah Al-Din Governorate, Iraq - Younus, Sinan Mezher (Journal of Science in Medicine and Life, 2024)
This study aimed to investigate the effect of transformational leadership on supporting Total Quality Management (TQM) initiatives in commercial banks operating in Salah Al-Din Governorate, Iraq. The research problem stemmed from the weak adoption of TQM concepts by many Iraqi banks despite increasing competitive challenges in the banking sector, necessitating an understanding of the role of transformational leadership in stimulating and implementing these initiatives. The study employed a descriptive-analytical approach, distributing a questionnaire to a stratified random sample of 285 employees from upper and middle management levels across eight major commercial banks in Salah Al-Din Governorate. Transformational leadership was measured through four dimensions: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. TQM was assessed through: customer focus, continuous improvement, total employee involvement, and data-driven decision making. Statistical analysis using multiple regression revealed a significant positive effect (P < 0.001) of transformational leadership on supporting TQM initiatives. The transformational leadership dimensions collectively explained 68.4% of the variance in TQM implementation (R² = 0.684). Intellectual stimulation had the strongest effect (β = 0.312, P < 0.001), followed by idealized influence (β = 0.287, P < 0.001), inspirational motivation (β = 0.241, P < 0.01), and individualized consideration (β = 0.198, P < 0.05). The study concluded that transformational leadership represents a critical factor in the successful implementation of TQM in commercial banks in Salah Al-Din Governorate. The study recommended developing specialized training programs to cultivate transformational leadership skills among managers, establishing organizational structures that support a culture of quality and innovation, and adopting incentive systems that encourage transformational leadership behaviors.